A onipresença do streaming: tecnologia, trabalho e ideologia por trás do “assista quando e onde quiser” - Jefferson Vieira de Góes (2024)
The streaming sector emerged from the ruins of the VHS and DVD industry, as the revolution in the technical base has made the maintenance of this form of capitalist exploitation unfeasible. Through appropriation of the technological development of the broadcasting/communications industry, streaming replaced workers (living labour) with technologies (dead labour), reduced the running time of films and series (in the past it was necessary to go to a video store, nowadays we just click play via cell phone) and expanded subscription commerce over title commerce. As the subscription is a commodity that supports the platform itself, and as content, films and series, both technological improvement and audiovisual production are at the center of the economic dynamics of streaming. Thus, this research aimed to investigate the technological, work and ideological aspects of the film and series streaming sector. Behind “watch whenever and wherever you want”, it was observed the production and growing usage of artificial intelligence (AI) to improve the platform, and also in audiovisual production activities such as the creation of scripts and subtitles, and even “digital” extras. These usages were on the agenda of the screenwriters and actors' strike in the USA in 2023, which in some way sought to “limit” the replacement of workers by AI. On the international scene, competition for subscriptions has led to a greater articulation of the sphere of production with that of circulation under the same private capital (on the one hand, Netflix and Amazon buying film studios, and on the other, the large studios producing their own platforms such as Disney+ and Globoplay), reducing the capital turnover time, engendering the formation of a global technical-financial complex and expanding audiovisual productions in non-English languages through outsourcing. The streaming sector has also invested in promoting its image linked to the values of diversity and inclusion, aiming to configure itself as a space for aesthetic representation and employment for workers from historically oppressed groups who are, first and foremost, consumers. However, it was observed the appropriation of these debates in favor of conforming, rather than combating oppression. The greater presence of men, both in the main positions of research and technology, and in cinema (direction and screenwriting), was reflected in the representation of men and women in Netflix's original Brazilian films (released until 2022). They were given, in addition to the role of teenage or young adventurer, the roles of mother or romantic partner of the main male character. Therefore, it is important to understand the ideological aspects produced by streaming, besides the relationship between work and technology, because films and series are important ideological vehicles and, as they are inseparable from the material soil that produced them, they are linked to a greater or lesser extent to the context of the class struggle.